Decadal extreme drought reduces alpine subsoil carbon stocks - Ronglei Zhou; Jinsong Wang; Quancheng Wang; Ning Liu; Chenglong Ye; Jingjing Shi; Mengjie Liu; Zhangwei Gao; Houkun Chu; Zhenrui Zhang; Bin Niu; Song Wang; et al. (Proceedings of the National Academy of Sciences, 2026)
Grassland soil organic carbon (SOC) stocks are increasingly vulnerable to intensified drought. Yet, how long-term, especially extreme, drought affects these C reserves across soil profiles remains unresolved. Here, we present the response of SOC stocks at various depths (0 to 60 cm) using an experiment involving a 10-year drought gradient (P, 1/2 P, 1/4 P, and 1/12 P, where P is ambient precipitation) in an alpine grassland. We found that extreme drought (1/12 P) caused significant SOC losses in the subsoil, whereas mild to moderate droughts had no significant effects on SOC at any depth. Under extreme drought, SOC stocks declined by 27% in the 20 to 30 cm layer and by 37% in the 30 to 40 cm layer, while no significant changes were observed in the topsoil (0 to 20 cm) and the deeper layer (40 to 60 cm). Subsoil C losses were primarily driven by reductions in mineral-associated organic C (MAOC) rather than particulate organic C. Multiyear extreme drought disrupted soil–microbe–mineral interactions, as indicated by reductions in soil nitrogen availability, microbial biomass, carbon use efficiency, and mineral-binding agents. These changes collectively undermined the formation and stabilization of MAOC. Our findings suggest that prolonged extreme drought can weaken subsoil C storage and stability, highlighting the need to incorporate subsoil processes into Earth System Models to better predict soil C–climate feedback under future drought scenarios.